1999
DOI: 10.1073/pnas.96.22.12345
|View full text |Cite
|
Sign up to set email alerts
|

A protein residing at the subunit interface of the bacterial ribosome

Abstract: Surface labeling of Escherichia coli ribosomes with the use of the tritium bombardment technique has revealed a minor unidentified ribosome-bound protein (spot Y) that is hidden in the 70S ribosome and becomes highly labeled on dissociation of the 70S ribosome into subunits. In the present work, the N-terminal sequence of the protein Y was determined and its gene was identified as yfia, an ORF located upstream the phe operon of E. coli. This 12.7-kDa protein was isolated and characterized. An affinity of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 17 publications
5
110
0
Order By: Relevance
“…In this paper, we call these proteins YfiA and YhbH, respectively. In the study by Agafonov et al (1999), YfiA was designated protein Y and was shown to bind to the 30S ribosomal subunit.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we call these proteins YfiA and YhbH, respectively. In the study by Agafonov et al (1999), YfiA was designated protein Y and was shown to bind to the 30S ribosomal subunit.…”
Section: Resultsmentioning
confidence: 99%
“…Residual dipolar couplings were determined as the difference between coupling constants in the aligned and isotropic conditions, and were incorporated at the late stage of structure calculation. One-bond 1 D CH values were converted to equivalent 1 D NH values. Data for residues with 1 H-15 N heteronuclear NOE values less than 0.6 were excluded from the structure calculations.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Furthermore, pY binds to the small ribosomal subunit in an Mg 2+ -dependent manner and becomes less exposed to solvent upon association of the small and large ribosomal subunits. This suggests an intersubunit position for pY in the 70S ribosome and may explain its ribosome stabilization effect [1]. pY inhibits translation most probably by interfering with the binding of the aminoacyltRNA to the ribosomal A site [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two protein factors with 40% sequence homology, HPF and YfiA (also known as RaiA or protein Y) (Agafonov et al 1999;Maki et al 2000), are involved in 100S formation and dissociation. HPF functions in the second step of the reaction, whereas YfiA functions in the dissociation of the 100S subunits (Ueta et al 2005).…”
Section: Introductionmentioning
confidence: 99%